Taksonometryczna analiza rynku pracy w województwie wielkopolskim w latach 2000-2003 - Witkowska, Aleksandra; Witkowski, Marek (Taxonomic analysis of labour market in Wielkopolska voivodeship between 2000 and 2003, 2006)
The paper presents a taxonomic analysis of labour market in the districts of Wielkopolska voivodeship between 2000 and 2003. The data for this analysis was obtained from the following publiccations, issued by the Statistical Office: „Essential data about districts and communes in Wielkopolska voivodeship” and „Labour market in Wielkopolska voivodeship. Years 2000 - 2004”. In this research, a method of synthetic variables was used. The build-up of its variables was based on the formula of the average normalized values of diagnostical variables and - as a comparison on the RANG method. The results of the research allow us to point out that the condition of the labour market in the Wielkopolska districts was very diverse. The best situation occured in poznański district, and the worst in jarociński and słupecki districts, respectively. Visibly fewer changes were noticed in the consecutive years, which allow us to make a thesis about the lack of compensatory actions taken by the voivodeship authorities to even the diversity of the labour market amongst districts. It can be stated, that the use of the method below in the research was justified both formally and essentially.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 127-143